Correlation and Regression Between Age and Body Weight on Semen Quality of Limousin Bulls in Artificial Insemination Center, Lembang, West Java - Muhamad Allabus Royan; Akhmad Dakhlan; Madi Hartono; Sri Suharyati (Buletin Peternakan, 2021)
This research aimed to determine the correlation and to find the best regression model for predicting semen quality (semen volume, individual motility, and sperm concentration) based on age and body weight in Limousin bulls. This research was conducted in December 2019 in Artificial Insemination Center, Lembang, West Java. The method used was a survey with census data collection, namely all Limousin bulls with semen collected were used in this study. The data were analyzed for correlation and simple and multiple regression using R program. The results showed that the average of age, body weight, semen volume, individual motility and sperm concentration were 58.36 ± 40.19 months, 807.12 ± 91.59 kg, 5.86 ± 1.31 ml, 67.59 ± 4.11%, and 1006.23 ± 145.28 million/ml, respectively. Age with semen volume, body weight with semen volume, and combination of age and body weight with semen volume, had a medium positive correlation (P<0.05), with a correlation coefficient of 0.52, 0.58 and 0.58, respectively. The regression model with the highest coeficient of determination value (R2) was between body weight and semen volume with regression equation of Ŷ = -0.8129 + 0.008269X and of R2 = 0.34. In conclusion, semen volume of Limousin bull could be estimated using their age and body weight, while individual motility and sperm concentration might not be able to be estimated using their age and body weight.